HYDATID DISEASE IN MISCULOSCELETAL TISSUES: DIAGNOSIS AND TREATMENT - Jovanoski, Slavko; Bogojevska Doksevska, Milena; Manasieva, Magdalena; Bakalovski, Stefan; Nikolovski, Nikola; Gjorgjioski, Daniel; Angelevski, Dimitar; Bede Stevoska, Sanja (Journal of Morphological Sciences, 2023)
Musculoskeletal hydatidosis is a rare occurrence of hydatid disease. Anatomical and clinical changes are, however, peculiar to this localization. Musculoskeletal hydatid disease is defined as development of multiple cysts within bone or soft tissue, that are the larval form of the tapeworm Echinococcus granulosus. Bone cysts account for only 0.5â€“2.5% of all hydatid cysts in humans. We present a case of 39-years-old male, presented at our clinic with one month duration of pain in his right calf. Previously, there was asymptomatic swelling that existed one year, but as it got painful, the patient decided to seek medical help. Bone tumors, tumor-like conditions, and specific and nonspecific infections should be considered as a possible differential diagnosis. The final diagnosis depends on histology. The treatment depends on surgical excision. Recurrence is common, particularly at sites that are difficult to access. Keywords : Echinococcosis, Hidatid bone disease, tumor-like conditions. https://doi.org/10.55302/JMS2361116j